Analisis Determinan Struktur Modal pada Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2014-2018 - Nani Hartati; Anissa Eka Fitria (President University Press, 2020)
The capital structure explains how the company funds its operational activities. The capital structure is influenced by various aspects, liquidity, profitability, company activity, asset structure and non-debt tax shield. The purpose of this study is to determine the effect of liquidity, profitability, activity, asset structure and non-debt tax shield on the capital structure of automotive companies listed on the IDX in the 2014-2018 period. Types of research is an explanatory research with quantitative method approach with a population of all automotive companies listed on the Indonesia Stock Exchange in 2014-2018. Purposive sample method is a sample selection method with a sample size of 6 sample companies. Multiple linear analysis is a data analysis method used with a significance of 5%. In this study, it can be concluded that CR, NPM and TATO have no effect on capital structure, while SA and NDTS have a significant positive effect on capital structure.